Investigation on Heat of Hydration of Concrete Containing Used Glass as Replacement of Fine Aggregate - Ravindran, Hena Niesha Bella; Jamellodin, Zalipah (Recent Trends in Civil Engineering and Built Environment, 2023)
Malaysia’s waste generation rate is rising, encompassing community activities such as commercial, academic, industrial, and business operations. It is also linked to the economic status of various community sectors such as squatter settlements, low, medium, and high-class residential neighbourhoods. This research aims to investigate the heat hydration of concrete consist of glass as partial replacement to fine aggregate. For determination of concrete hydration temperature, plywood with size 300 mm x 300 mm x 450 mm cube was used as the exterior mould. It was packed with 150 mm thick polystyrene acting as the insulator. Polyvinyl chloride (PVC) pipe with diameter of 150 mm and a height of 300 mm is used to fill the concreter mix. A thermocouple (Type K) was inserted into the centre of each box and was connected to a data logger system. Temperature rises due to heat of hydration in all mixes were recorded for 72 hours. The results revealed that the replacement of glass with fine aggregate will slightly reduce the temperature. The most effective percentage of replacement is 25% with 36.18 °C heat.